Chronic pain in blunt chest wall trauma: A pilot study. (October 2016) - Battle, Ceri E; Young, Katie; Evans, Phillip A
Introduction: Blunt chest wall trauma is commonly recognised as a significant source of acute pain following injury but the longer term outcomes in this patient cohort are less well described. The aim of this pilot study was to investigate the incidence of chronic pain in patients with isolated blunt chest wall trauma, with or without rib fractures. Methods: A short survey was completed over the phone, or as a postal survey. The emergency department medical records and hospital database were used to obtain the demographic data, including patient age, pre-existing conditions, trauma sustained, hospital and intensive care unit length of stay, mechanical ventilation days and mortality. Patients' demographics were analysed using descriptive statistics and Mann–Whitney U and Fisher's exact tests for comparison of variables. Results: A total of 100 patients were admitted to hospital with isolated blunt chest wall trauma in 2014, with 67 patients eligible for inclusion in the study; 40 patients responded to the survey (60% response rate). Chronic pain was reported in 14 (35%) patients with a median pain severity score of 6 out of 10 (IQR: 3–7). The only significant predictor of chronic pain was if the patient's mechanism of injury was an assault. Discussion: The results of this pilot study have demonstrated that a high percentage of isolated blunt chest wall trauma patients suffer chronic pain at six months or more post-injury. Assault was the only predictor of chronic pain. Further prospective studies are required to evaluate the long-term outcomes following blunt chest wall trauma.